The Law and Economics of Judicial Systems - Shavell, Steven (World Bank, Washington, DC, 2012)
The economic analysis of law is an indispensable conceptual tool for designing and reforming legal systems. It does not necessarily deal with markets, prices, and what are conventionally thought to be economic concepts. Rather, it is an approach to analyzing the law and legal institutions that focuses on systematic, empirical analyses of the incentives and effects created by alternative legal constraints. The economic analysis of law can also be a valuable tool in considering alternative models for reforming legal institutions. Three broad principles of reform are suggested by this approach: reducing the scope of the law, simplifying the law, and using incentives to alter access to the legal system. Reformers and social planners should always consider the possibility of reducing the scope of the law. Reducing the demand for legal services can free much human talent for other things--the practice of medicine, the construction of roads, and so on. Since legal rules can become very complicated, simplifying them may save scarce resources. One way to drastically reduce the amount of litigation is to use predetermined schedules or tables to calculate the damages that accident victims can collect rather than making the amount a subject for legal adjudication. Lastly, there are important externalities to the use of legal services, and policymakers should not allow private actors alone to determine when they want to bring suits.